Penggunaan Prinsip Kerja Sama pada Novel Yougisha X No Kenshin Karya Keigo Higashino - Adna, Muhammad Defa; Ngurah Indra Pradhana (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This study is entitled "The Application of the Cooperative Principle in the Novel Yougisha X no Kenshin by Keigo Higashino." The aim of this research is to analyze the forms of the cooperative principle and its violations. The study adopts a pragmatic approach by employing Grice’s (1975) theory of the cooperative principle. A qualitative descriptive method was used, with reading and note-taking techniques for data collection. The findings indicate that all four maxims of the cooperative principle—quantity, quality, relevance, and manner—are found in both compliance and violation within the dialogues between characters.